Torovirus infection in animals: a review - V. А. Mischenko; A. V. Mischenko; T. B. Nikeshina; Yu. V. Brovko; А. I. Kushlubaeva (Ветеринария сегодня)
Massive digestive disorders of neonatal calves, clinically manifested as diarrhea causing severe dehydration, toxemia, immunodeficiency and metabolic disorders, induce huge economic losses in animal husbandry. Etiopathogenetic lesions of the digestive organs are characterized by significant polymorphism, including a wide range of various (physiological, sanitary and infectious) factors. Massive gastroenteritises in neonatal calves are primarily caused by such infectious agents as viruses, bacteria and protozoa. Massive diarrheas are registered in 70–80% of newborn calves by the end of the first day of life. Diseased newborn calves die on day 5–10 and mortality ranges from 15 to 55%. Rotavirus, coronavirus, pestivirus, parvovirus, enterovirus and kobuvirus, along with bacteria, are most frequently detected in faecal samples collected from neonatal calves with diarrhea. Diagnostic and vaccine products for prevention of these infections have been developed in the Russian Federation. At the end of the 20th – the beginning of the 21st century a large number of cattle were imported to Russia from the countries affected with different contagious diseases (USA, Denmark, France, Slovakia, Austria, Hungary, Germany, the Netherlands, Australia, Finland, etc.). Despite the high activity and field effectiveness of vaccines against rotavirus and coronavirus infections and viral diarrhea, massive neonatal calf diarrheas causing significant economic losses were registered in a number of large-scale livestock farms. Torovirus as well as the above-mentioned pathogens were detected in fecal samples from diseased calves. This report provides data on torovirus infection indicating a wide geographical distribution of animal torovirus in many countries of the world. All this suggests the need to take into account torovirus infection when conducting epizootological investigations in farms affected with massive gastrointestinal diseases of neonatal calves.